2014
DOI: 10.1016/j.btre.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity of different parts of the plant Lepidium sativum Linn

Abstract: Lepidium sativum Linn. has been used in traditional and folklore medicine for the treatment of bronchial asthma, diabetes, local and rheumatic pain. An ethanolic extract of cress (L. sativum L.) shoot, leaf, stem and seed has been studied for antioxidative active against 1,1-diphenyl-2-picrylhydrazyl (DPPH), total glutathione S-transferase assay, reduced glutathione activity, reducing power (Fe3+–Fe2+ Transformation Ability), and ascorbic acid is also estimated. The percentage yields of free radical scavenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…38 This may be attributed to the phenolic compound gallic acid and other groups of phytochemical constituents present in it 36,39 . Similar results have been reported for the ethanolic extract of Terminalia glaucescens flowers, 40 different plant parts of Lepidium sativum, 41 and Mollugo nudicaulis. 42 …”
Section: Standardization Of the Ethanolic Extract Of Mefsupporting
confidence: 76%
“…38 This may be attributed to the phenolic compound gallic acid and other groups of phytochemical constituents present in it 36,39 . Similar results have been reported for the ethanolic extract of Terminalia glaucescens flowers, 40 different plant parts of Lepidium sativum, 41 and Mollugo nudicaulis. 42 …”
Section: Standardization Of the Ethanolic Extract Of Mefsupporting
confidence: 76%
“…Malar et al. () analyzed different parts of cress plants and concluded that shoot extract has the highest amount of ascorbate. Lisjak et al.…”
Section: Biostimulant Effects On Edible Horticultural Speciesmentioning
confidence: 99%
“…40 The free radical scavenging activity of the L. sativum seed methanolic extract was investigated and it was concluded that free radical scavenging activity of the extract may be attributed to the polyphenolic compounds which have the ability to scavenge free radicals and enhance the DNA repair system or DNA synthesis. 32,41 Also, Malar et al, 42 showed that the ethanolic extracts of L. sativum seed extract exhibited high antioxidant activities and therefore form a potential source of natural antioxidant compounds.…”
Section: Discussionmentioning
confidence: 99%